Social formations in the medieval world: From Roman civilization till the crisis of feudalism - Kumar, Rakesh (Historian) (Abingdon, Oxon; New York, USA: Routledge, 2024)
"This book encapsulates a period of history of human progress by highlighting crucial social, economic, and cultural dynamics. It presents recent historiography and new analytical tools used to analyze multi-dimensional themes involved in social formation. This is a reader-friendly book with simple and lucid language and fulfils the pressing needs of students studying the paper on Social Formations and Cultural Patterns of Ancient and Medieval World at various universities across the world. The summary, keywords, and representative questions at the end of each chapter would assist in revision and better understanding of the issues dealt therein. A detailed chapter-end reference would enable and motivate the readers to engage in further studies for better understanding of the themes. This book will be of interest to students, researchers, and academics in the area of history - ancient and medieval world history in particular and anthropology. It will also be an interesting read for general readers interested in knowing about the ancient and medieval world"--
Ancient Rome I : Rome under republic, principate and empire -- Ancient Rome II -- Feudal polity, society and economy in Europe (8th-14th centuries) -- Religion and culture in medieval Europe -- Origin and growth of Islamic civilisation.
Includes bibliographical references and index.
Keywords: Social history -- To 500.; Civilization; Social history -- Medieval, 500-1500.; Civilization, Medieval; Islamic civilization; Religion and civilization; Rome -- Social conditions